Educational Implications of the Winter Season’s Provisions in the Light of Islamic Education - Alhizan, Mashael Raja; Matar, Rasha Ghazi; Aljuhani, Hanna Hamed; Atya, Belqes Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2023)
The research aims to highlight the educational implications of the universal verses related to the winter season, to clarify the educational implications of the worships related to the winter season. The research has adopted the fundamental approach. The study consisted of three chapters: the first chapter included the general framework of the study, the second chapter included a statement of the educational implications of the universal verses for the provisions of the winter season, and the third chapter contained a statement of the educational implications of the hadiths regarding the provisions of the winter season in worship, the study concluded with the findings and recommendations. The most important findings of the study were; The educational implication in the fact that winter is the booty of the worshipers, the educational implication in describing the fire of Hell with Zamhrir (simulation and description), the educational implication in changing the atmosphere from the signs of the small hour for numbers and preparation, from the hadiths of worship in the winter season, an indication of the mercy of God Almighty in judging the servants, the research recommends that take advantage of the winter season to draw closer to God Almighty with the types of acts obedience and worship.